Los derechos de la generación electrónica en el ámbito laboral - Aba Catoira, Ana (Revista de Derecho, 2019)
The aim of this paper is to provide readers with the legal situation of the exercise ofworkers’ fundamental rights through electronic means. The idea is to contextualizethe traditional conflict between the workers’ rights and the entrepreneurial controlfaculties in a framework characterized by the use of Information and CommunicationTechnologies to communicate, work and produce. The absence of specific regulationin this matter is a source of constant conflicts which courts have had to resolve dueto the numerous litigations posed by the imposing of disciplinary measures for theimproper and abusive use of these tools in the work place.
Keywords: ICTs; workers’ fundamental rights; entrepreneurial control faculties; Internet; entrepreneurial control facultieselectronic mail; electronic mail